Development of currency exchange rate tracking system - Phan, Zhan Yan (2024)
Currency exchange rate tracking systems are responsible to provide visualization for price movements of multiple pairs of currencies. In this day and age of rapid globalization, tracking currency exchange rates has become an integral part of most people’s daily routines. However, there are some potential issues with existing currency exchange rate tracking applications in the market which are complex interfaces which are non-beginner friendly, insufficient data visualization, and lack flexibility in creating the exchange rate notification alert. To address all the issues mentioned above, the currency exchange rate tracking system developed in this system uses a dashboard design to summarize the currency exchange rate performance for users to obtain as many insights as possible at first glance. Besides that, the system is embedded with an alert management screen for users to perform CRUD actions on the alerts. Lastly, the system uses various data visualization charts like line charts, bar charts, and heatmaps to convey information to the users. The proposed system is developed using prototyping methodology with Flask being the backend server. After the development stage, unit testing, integration testing, user acceptance testing, and usability testing are conducted to evaluate the functionality and usability of the output system the test results are documented in the report.